2024
DOI: 10.1007/s00259-024-06630-z
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant holmium-166 radioembolization after radiofrequency ablation in early-stage hepatocellular carcinoma patients: a dose-finding study (HORA EST HCC trial)

Pim Hendriks,
Daphne D. D. Rietbergen,
Arian R. van Erkel
et al.

Abstract: Purpose The aim of this study was to investigate the biodistribution of (super-)selective trans-arterial radioembolization (TARE) with holmium-166 microspheres (166Ho-MS), when administered as adjuvant therapy after RFA of HCC 2–5 cm. The objective was to establish a treatment volume absorbed dose that results in an absorbed dose of ≥ 120 Gy on the hyperemic zone around the ablation necrosis (i.e., target volume). Methods In this multicenter, prospective d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Another study evaluated an adjuvant selective infusion of 166 Ho-microspheres after RFA for the treatment of HCC and showed that it can be administered safely at a dose of 90 Gy to the treatment volume while reaching a dose of ≥120 Gy to the target volume. It may be a favorable adjuvant therapy for HCC lesions 2–5 cm [ 26 ].…”
Section: Local and Locoregional Therapiesmentioning
confidence: 99%
“…Another study evaluated an adjuvant selective infusion of 166 Ho-microspheres after RFA for the treatment of HCC and showed that it can be administered safely at a dose of 90 Gy to the treatment volume while reaching a dose of ≥120 Gy to the target volume. It may be a favorable adjuvant therapy for HCC lesions 2–5 cm [ 26 ].…”
Section: Local and Locoregional Therapiesmentioning
confidence: 99%